Loss of ferritin‐positive microglia relates to increased iron, RNA oxidation, and dystrophic microglia in the brains of aged male marmosets. Issue 2 (18th February 2019) - Rodríguez‐Callejas, Juan de Dios; Cuervo‐Zanatta, Daniel; Rosas‐Arellano, Abraham; Fonta, Caroline; Fuchs, Eberhard; Perez‐Cruz, Claudia
Abstract : Microglia are cells that protect brain tissue from invading agents and toxic substances, first by releasing pro‐inflammatory cytokines, and thereafter by clearing tissue by phagocytosis. Microglia express ferritin, a protein with ferroxidase activity capable of storing iron, a metal that accumulates in brain during aging. Increasing evidence suggests that ferritin plays an important role in inflammation. However, it is not known if ferritin/iron content can be related to the activation state of microglia. To this end, we aimed to delineate the role of ferritin in microglia activation in a non‐human primate model. We analyzed brains of male marmosets and observed an increased density of ferritin+ microglia with an activated phenotype in hippocampus and cortex of old marmosets (mean age 11.25 ± 0.70 years) compared to younger subjects. This was accompanied by an increased number of dystrophic microglia in old marmosets. However, in aged subjects (mean age 16.83 ± 2.59 years) the number of ferritin+ microglia was decreased compared to old ones. Meanwhile, the content of iron in brain tissue and cells with oxidized RNA increased during aging in all hippocampal and cortical regions analyzed. Abundant amoeboid microglia were commonly observed surrounding neurons with oxidized RNA. Notably, amoeboid microglia were arginase1+ and IL‐10+, indicative of a M2 phenotype. Some of those M2 cells also presented RNA oxidation and a dystrophic phenotype. Therefore, our data suggest that ferritin confers protection to microglia in adult and old marmosets, while in aged subjects the decline in ferritin and the increased amount of iron in brain tissue may be related to the increased number of cells with oxidized RNA, perhaps precluding the onset of neurodegeneration. Abstract : Ferritin protects M2 microglia against reactive oxygen species (ROS) produced during iron oxidation and during the phagocytic process (A). In adult (mean age 5.33 ± 0.88 years) and old (mean age 11.25 ± 0.7 years) marmoset brain, we observed a drastic decreased of microglia containing ferritin, whereas most microglia showed M2 phenotype. (B) Aged marmoset (mean age 16.83 ± 2.59 years) showed dystrophic microglia and RNA oxidative damage, whereas there was a significant increase of iron in brain tissue. It is known that increased RNA oxidation induce ferritin proteosomal degradation, by inactivating c‐aconitase promoting the inhibition of ferritin synthesis by IRP2/IRE regulatory system. Thus, we propose that iron/ferritin imbalance in aged marmoset can lead to oxidative damage and might be related to increased number of dystrophic microglia.